Problematika Pendidikan Agama Islam di Universitas Khairun Ternate - Bujuna Alwi Alhadad; Mizna Laila Albaar; Syarifuddin Ondeng (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
The aim of the research is to look at the problems of Islamic religious education in Public Higher Education and solutions to these problems in this paper focusing more on State Universities in North Maluku Province, namely Khairun University, PAI hopes that colleges and universities can understand and realize religious education courses as a compulsory subject that is the spirit of fostering student personality and the spiritual foundation for the development of their respective fields of knowledge. In this study the method used is the method that researchers use in this study is phenomenology. The phenomenological approach is an approach based on the idea and assumption that human experience is obtained through the interpretation of objects, people, situations and events, but their interpretation. The results of the research are that the development of PAI is an implication of the learning process on campus, requiring the development of faith values in students' attitudes and behavior that can be applied in life. The development of PAI at PTU needs to be updated starting from the cognitive learning process to instilling Islamic values in students so that they can have a positive impact on student self-development.